Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam - Imroatun Imroatun; Ine Nirmala; Juhri Juhri; Birru Muqdamien (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This literature research aims to add insight for parents of dual careers in caring for children independently or empowering other parties. All the considerations in it must refer to the Quran and Hadith. Including efforts to achieve the ideal parenting style. Parenting provided by parents to children has a variety of models and patterns between one family and another family. The main factors that influence in the form of changes in the position and relationship of parents and families with children. Keyword: parenting; children; IslamReferensiAl Amin, M. N. K. (2018). Komunikasi sebagai Upaya untuk Membangun Ketahanan Keluarga dalam Kajian “Teori Nilai Etik. Al-Ahwal: Jurnal Hukum Keluarga Islam, 11(1), 79–90.Amin, M. N. K. Al. (2013). Keluarga Sebagai Dasar Pendidikan Bagi Anak. Insania: Jurnal Pemikiran Alternatif Kependidikan, 18(1), 49–62. http://www.ejournal.iainpurwohttp//www.ejournal.iainpurwokerto.ac.id/index.php/insania/article/view/1443kerto.ac.id/index.php/insania/article/download/1443/1045Baumrind, D. (1991). The Influence of Parenting Style on Adolescent Competence and Substance Use. The Journal of Early Adolescence, 11(1), 56–95. https://doi.org/10.1177/0272431691111004Bisri, M. (2016). Mengembangkan Kesantunan Anak Dengan Gaya Pengasuhan Orangtua Baumrind. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 79–88.Daradjat, Z. (1985). Membina Nilai-nilai Moral Di Indonesia. Bulan Bintang.Fatihah, N., & Difla Nadjih. (2017). Hubungan Pendidik Dan Terdidik Dalam Al-Quran. Ulumuddin: Jurnal Ilmu-Ilmu Keislaman, 7(2), 73–86. https://jurnal.ucy.ac.id/index.php/agama_islam/article/view/188Gustian, D., Erhamwilda, & Enoh. (2018). Pola Asuh Anak Usia Dini Keluarga Muslim Dengan Ibu Pekerja Pabrik. Ta’dib: Jurnal Pendidikan Islam, 7(1), 21–34. https://doi.org/10.29313/tjpi.v7i1.3532Hadi, S. (2017). Pola Pengasuhan Islami Dalam Pendidikan Keluarga (Penguatan Peran Keluarga Jamaah Masjid Baitul Abror Teja Timur). TADRIS: Jurnal Pendidikan Islam, 12(1), 117. https://doi.org/10.19105/tjpi.v12i1.1290Helmawati. (2014). Pendidikan Keluarga Teori Dan Praktek. Rosdakarya.Hidayat, F. (2016). Pengasuhan Anak Usia Dini Dalam Perspektif Psikologi. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 1–4.Hidayat, F., & Imroatun, I. (2017). Keluarga Berencana Dan Pengasuhan Anak Usia Dini Di Indonesia Perspektif Psikologi. In A. dkk. (Ed.), Book Two International Conference Proceeding: Konsepsi dan Implementasi Pendidikan Islam Anak Usia Dini (Issue 52, pp. 164–171). IAIN Pontianak.Hyoscyamina, D. E., & Dewi, K. S. (2012). Pengembangan Program Parenting Bagi Anak Usia Dini Dengan Pendekatan Psikologi Positif Dan Karakter Islami.Imroatun, I. (2016). Subjective Consciousness of The Raudlatul Athfal Childhood on Playing. Proceeding The 1 Annual International Conference on Islamic Early Childhood Education, 1(December), 139–148.Jus’at, I., & Jahari, A. B. (2000). Review Antropometri Secara Nasional dan Internasional. Kumpulan Makalah Diskusi Pakar Gizi.Lamborn, S. D., Mounts, N. S., Steinberg, L., & Dornbusch, S. M. (1991). Patterns of Competence and Adjustment among Adolescents from Authoritative, Authoritarian, Indulgent, and Neglectful Families. Child Development, 62(5), 1049. https://doi.org/10.2307/1131151Mansur. (2011). Pendidikan Anak Usia Dini Dalam Islam. Pustaka Pelajar.Morrison, G. S. (2012). Dasar-Dasar Pendidikan Anak Usia Dini (PAUD). PT Indeks.Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. http:// repository.uinbanten.ac.id/1420/9/09 - Prosiding PGRA - Difla Nadjih.pdfNurjidin, & Nugroho, T. (2016). Mendidik Anak Usia Dini ( Analisis Sosiologi Keluarga ). Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 65–78.Padjrin, P. (2016). Pola Asuh Anak dalam Perspektif Pendidikan Islam. INTELEKTUALITA, 5(1), 1–14. https://doi.org/10.19109/ intelektualita.v5i1.720Prasetyaningrum, J. (2012). Pola Asuh Dan Karakter Anak Dalam Perspektif Islam. Prosiding Seminar Nasional Psikologi Islami.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin: Jurnal Ilmu-Ilmu Keislaman, 9(1), 49–60. https:// jurnal.ucy.ac.id/index.php/agama_islam/article/view/283Putranti, S. D. (2008). Pola Pengasuhan Anak Pada Keluarga Karir Ganda. Jurnal Psikosains, 2, 44–62.Rahayu, I. T. (2005). Pola Pengasuhan Islami Sebagai Awal Pendidikan Kecerdasan Emosional. Psikoislamika : Jurnal Psikologi Dan Psikologi Islam, 2(2), 162–171. https://doi.org/ 10.18860/psi.v0i0.339Santrock, J. W. (2007). Child Development (M. Rachmawati & A. Kuswanti (trans.); 11th ed.). Erlangga.Ulwan, A. N. (1992). Pendidikan Anak Menurut Islam Pendidikan Sosial Anak. Rosdakarya.Uyuni, Y. R. (2019). Konsep Pola Asuh Orang Tua Dalam Perspektif Islam Terhadap Tumbuh Kembang Anak Dalam Keluarga. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 53–64.